Political crisis blocks (Venezuela) - Voidly (2019)
CRITICAL severity censorship detected in Venezuela. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: VE-2019-0001
Keywords: censorship; VE; censorship; critical